The Exhumation of the Northern Patagonian Massif Gondwana Planation Surface Due to Uprising During the Oligocene - Aragón, Eugenio (2014)
Fil: Aragón, Eugenio. Centro de Investigaciones Geológicas (CIG). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata